Penggunaan Media Pembelajaran Audio Visual Terhadap Hasil Belajar Maeri Bnagun Ruang - Peby Irma Pujiasih; Widya Permata Dilla; Holten Sion (PGSD FKIP UPR, 2023)
This study aims to describe the influence of the use of audio-visual learning media on the learning outcomes of building space materials. This research is a quantitative research. This type of research is experimentalÂ research. The research design used was One-group pretest-posttest design. The subjects of this study were class V students totaling 23 students, the sampling technique carried out in this study was a total sample or the entire population was sampled, so the sample used amounted to 23 students. This data collection uses test results in the form of pretest and posttest and documentation. The data analysis technique used is parametric statistics with t-test analysis. The calculation results using SPSS version 25 using paired sample t-test showed Sig. (2-tailed) value 0.000<0.05. This is also evidenced by the results of the t-test calculation, it is known that the t-count is 6,781 and the t-table is 1,717. Based on the test results, it is stated that t-count > t-table (6,781>1,717). Through the data obtained, it can be concluded that Ha wasÂ accepted, meaning that there is an influence on the use of audio-visual learning media on the learning outcomes of building space materials in grade V students of SDN 5 Langkai Palangka Raya.